Spending habits among undergraduates student in Universiti Teknologi MARA (UiTM) Samarahan 2 / Nur Fatin Amira Ruzani - Ruzani, Nur Fatin Amira; Zamhari, Siti Naemah (2018)
"According to (Kennett-Hensel, Neelev and Min. 2011) they stated that Generation Y are viewed "as a generation with very high buying power" as they have annual incomes totalling USD211 billion and spend USD39 billion per year (Nowak. Thach and Olsen 2006). In (Visa USA Inc.. 2007) statistics it stated that by 2015 Generation Y will account for approximately USD2.45 trillion in annual spending. Therefore, businesses across all industries will need to know and appreciate the qualities and values of the Gen Y and being sensitive to their needs willed be the key factor in expanding current businesses." In addition, spending money is a big part of our daily life. Smart spending habits keep the student from paying too much for an item, needs and wants. Students tend to overspend their saving for their course activities. lecture session, assignment, shopping and any other social problems around them. Apart from that, living in a college is a change from youth into adulthood that makes student life more difficult and harder because they- have to settle on a choice for themselves. In the ages past, book stationeries, clothes, and other comparative things for study were bought by the students. In the present time, student's needs have expanded without a doubt, when tablets and others gadgets are required for assignments and for a few vehicles outside the essential necessities that a student should possess. For students that having a bad financial literacy and not well in organizing their own money tend to get stressed as they will try hard to find the money for their daily use from many sources.